National Smoking Cessation Services (NSCS) enrollment and their effect on long-term tobacco cessation in Korea: Results from a 1-year prospective follow-up of NSCS participants - Jinju Park; Min Kyung Lim; Yunhee Kim; Yu-Jin Paek; Sung-il Cho (Tobacco Induced Diseases, 2024)
Introduction The study aimed to identify predictors associated with long-term tobacco cessation at 12-month follow-up among users of the National Smoking Cessation Services (NSCS) in Korea.